2023
DOI: 10.1007/s10899-023-10203-4
|View full text |Cite
|
Sign up to set email alerts
|

Designing Improved Safer Gambling Messages for Race and Sports Betting: What can be Learned from Other Gambling Formats and the Broader Public Health Literature?

Abstract: Safer gambling messages are one potential input to a public health approach toward reducing gambling-related harm, and yet there is no strong evidence supporting current messages such as “gamble responsibly” or “keep the fun in the game”. Furthermore, sports betting is increasing in popularity in multiple jurisdictions, such as Australia and the US, increasing the need to design effective messaging campaigns for race and sports betting. Compared to other gambling formats, such as electronic gambling machines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Moreover, the dominant discourse of “responsible gambling” has been recently criticized, as it is an industry-friendly discourse, attributing the responsibility of gambling-related harm to the consumers and ignoring the harm production capacity of gambling products (Livingstone & Rintoul, 2020; Newall, Rockloff, et al, 2023). Research has shown that this responsible gambling discourse, by focusing on personal responsibility, increases felt and enacted stigma among people who experience gambling problems, as well as feelings of personal blame and shame (Miller & Thomas, 2018).…”
Section: Challenging “Responsible Gambling” Prevention Messagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the dominant discourse of “responsible gambling” has been recently criticized, as it is an industry-friendly discourse, attributing the responsibility of gambling-related harm to the consumers and ignoring the harm production capacity of gambling products (Livingstone & Rintoul, 2020; Newall, Rockloff, et al, 2023). Research has shown that this responsible gambling discourse, by focusing on personal responsibility, increases felt and enacted stigma among people who experience gambling problems, as well as feelings of personal blame and shame (Miller & Thomas, 2018).…”
Section: Challenging “Responsible Gambling” Prevention Messagesmentioning
confidence: 99%
“…Moreover, the dominant discourse of "responsible gambling" has been recently criticized, as it is an industry-friendly discourse, attributing the responsibility of gambling-related harm to the consumers and ignoring the harm production capacity of gambling products (Livingstone & Rintoul, 2020;Newall, Rockloff, et al, 2023).…”
Section: Challenging "Responsible Gambling" Prevention Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that such messages are ineffective in reducing harmful gambling (Newall, Hayes, et al, 2023;Newall, Weiss-Cohen, Singmann, Walasek, & Ludvig, 2022). Despite subsequent calls for improvements in the quality, visibility, and frequency of harm-reductive messaging in gambling marketing (Newall, Rockloff, et al, 2023), there appears to have been no substantial increase or improvement in such messaging within English football since 2020 (Purves et al, 2020).…”
Section: ) Other Formatmentioning
confidence: 99%
“…Historically, these messages usually emphasise gambling as a personal choice (Miller & Thomas, 2018). Although there is not a lot of evidence that these general messages work (Newall, Hayes et al, 2023;Newall, Rockloff et al 2023;Newall, Weiss-Cohen et al 2022), some research has found pop-up messaging on electronic gambling machines (EGMs) to be moderately effective, at least in the short-term (Bjørseth et al, 2020), particularly those that encourage self-appraisal (McAuliffe et al, 2021). These pop-up messages can focus on general advice or specific advice targeted to the gambler's circumstances (e.g., "You're playing faster than most people."…”
Section: Introductionmentioning
confidence: 99%